Tindakan Rasional Instrumental Peternak Lokal Dalam Penanganan Penyakit Newcastle Disease Pada Ternak Ayam: Instrumental Rational Action of Local Farmers in Handling Newcastle Disease in Chicken Livestock - Widayati, Okti; Purwanta, Purwanta; Ampnir, Toni Alex (Fakultas Peternakan Universitas Jambi, 2025)
Background: Newcastle Disease (ND), also known as Tetelo disease, is one of the important viral diseases in poultry that causes high morbidity and mortality. This disease case attacks poultry which is widely kept by the community. Newcastle Disease can be prevented and treated when the public has knowledge about ND disease. Purpose: This study aims to determine the instrumental rational actions of local farmers against Newcastle Disease or tetelo in chicken livestock and the level of knowledge of farmers on the handling and management of Newcastle Disease or tetelo in chickens. Methods: The research used a qualitative approach. The variables and indicators of measuring farmers' instrumental rational action strategies against Newcastle Disease are about health handling, treatment, prevention, cage sanitation, and quarantine measures. The data sources were primary and secondary data which obtained by means of observation, interviews, and filling out questionnaires. The level of knowledge of farmers is measured by providing pretest and post-test questionnaires. The counseling activity was attended by 30 respondents using a folder tool. Qualitative data was presented in descriptive form, while data on improving farmers' knowledge was analyzed using the T-test. Results: Based on the results, 43.33% separated sick chickens, 66.67% treated sick chickens, 43.33% treated dead chickens, and 43.33% took preventive measures against ND disease. The results of the extension evaluation showed an increase in knowledge (p<0.05) with the results of the effectiveness of increasing knowledge in the category of quite effective. Conclusion: Most of local breeder have implemented measures to handle ND disease according to standards. With counseling about ND disease, it can increase public knowledge.